Metal soprtion enhancement of rice hull through chemical modification - Low, K. S.; Lee, C. K.; Wong, S. Y.; Tang, P. L. (Taylor and Francis Group, 2000)
Various chemical modifications were attempted on rice hull in order to improve its metal sorption capacity. Ethylenediamine tetraacetic acid (EDTA) was found to give the greatest enhancement. Parameters investigated include pH, initial concentration, sorbent dosage and competition with other cations and chelators. Sorption was pH dependent with greater uptake at higher pH value. Equilibrium was attained in less than 60 minutes implying the material could be suitable for continuous flow system. Maximum sorption capacities of EDTA-modified rice hull were 8.86, 9.59, 8.76 and 28.65 mg g−1 for Cu(II), Cr(III), Ni(II) and Pb(II) respectively. The presence of EDTA and nitrilotriacetic acid (NTA) suppressed the metal binding capacity of EDTA-RH. Column study on the removal of Cu(II) from wood preservative waste showed that the removal of Cu(II) was a function of bed-depth.